Effect of Plane of Nutrition on Blood Biochemical Profile and Reproductive Efficiency in Nili Ravi Buffalo Heifers - MAVI, P S; BAHGA, C S; SINGH, NARINDER; NAYYER, SHASHI (The Indian Journal of Animal Reproduction, 2023)
Fifteen Nili Ravi heifers aged I 3 months were randomly divided into three groups of 5 each.Group-I was fed I 00%, Group-II II 5% and Group-II1 130% of nutrients as per the Kearl (1982) feedingstandards. Blood samples were collected at fortnightly intervals. Haemoglobin and haematocrit did notdiffer significantly in the three groups. Blood glucose levels in Groups I, II and Ill were 70.15± 1.67,67.15± 1.67 and 65.25± 1.67 mg %, respectively. The differences were significant {P
Keywords: Heifers; Feeding level; Puberty and conception